Effect of Family Nursing Intervention on Suffering Parents of Children with Cancer: A Quasi-Experimental Study - Chintana Wacharasin; Natchanan Chivanon; Sivasankari Nadarajan (Iranian Journal of Nursing and Midwifery Research)
Background: Childhood cancers often lead to significant distress for parents. This study aimed to evaluate the effects of a Family Nursing Intervention (FNI) on the suffering of parents of children with cancer. Materials and Methods: This study employed a quasi-experimental design with a sample of 42 parents of children with cancer. The experimental group participated in a four-week FNI program with weekly 90-minute sessions, while the control group received only routine care. Data were collected using a parenting suffering scale at baseline and after the intervention and analyzed using descriptive statistics and t-tests. Results: This study showed that, at post-test, the parents who participated in the FNI had significantly lower suffering scores compared to those in the control group (t37.60= −3.45, P = 0.001). Conclusions: These findings suggest that FNI could alleviate parents’ suffering in similar contexts in the future.